2016
DOI: 10.1097/qai.0000000000000848
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception, Pregnancy, Breastfeeding, and Risk of HIV Disease Progression Among Zambian Women

Abstract: Background Some studies suggest hormonal contraception, pregnancy, and/or breastfeeding may influence rates of HIV disease progression. Methods From 1994-2012, HIV discordant couples recruited at couples' voluntary HIV counseling and testing centers in Lusaka were followed 3-monthly. Multivariate survival analyses explored associations between time-varying contraception, pregnancy, and breastfeeding and two outcomes among HIV-positive women: 1) time-to-death and 2) time-to-antiretroviral treatment (ART) init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…33 The primary study objectives were to evaluate correlates of HIV acquisition and transmission. The study recruitment, 34,35 intervention design, uptake of contraception immediately after an educational intervention, 36 effect of informed consent on knowledge and concerns about contraceptive methods, 37 demographics of the cohort, rates of unintended pregnancy and effect of contraceptive method on unintended pregnancy, 38 effect of the intervention on incident pregnancy, 39 patterns of contraceptive use and discontinuation, 40 effect of hormonal contraception on HIV acquisition risk 41 and HIV transmission to partners, 42 and effect of hormonal contraception on HIV disease progression 43 have been reported previously. This study was approved by the Institutional Review Boards at Emory University and the University of Zambia.…”
Section: Methodsmentioning
confidence: 99%
“…33 The primary study objectives were to evaluate correlates of HIV acquisition and transmission. The study recruitment, 34,35 intervention design, uptake of contraception immediately after an educational intervention, 36 effect of informed consent on knowledge and concerns about contraceptive methods, 37 demographics of the cohort, rates of unintended pregnancy and effect of contraceptive method on unintended pregnancy, 38 effect of the intervention on incident pregnancy, 39 patterns of contraceptive use and discontinuation, 40 effect of hormonal contraception on HIV acquisition risk 41 and HIV transmission to partners, 42 and effect of hormonal contraception on HIV disease progression 43 have been reported previously. This study was approved by the Institutional Review Boards at Emory University and the University of Zambia.…”
Section: Methodsmentioning
confidence: 99%
“…Heterosexual married or cohabitating HIV serodiscordant couples were invited to enroll in an open cohort study between 1994 and 2012. The study recruitment [ 25 , 26 ], intervention design, uptake of contraception immediately after an educational intervention [ 27 ], impact of informed consent on knowledge and concerns about contraceptive methods [ 28 ], demographics of the cohort, rates of unintended pregnancy and impact of contraceptive method on unintended pregnancy [ 29 ], impact of the intervention on incident pregnancy [ 30 ], patterns of contraceptive use and discontinuation [ 31 ], impact of hormonal contraception on HIV acquisition risk [ 7 ], HIV transmission to partners [ 32 ], and disease progression [ 33 ] have been previously reported. The Institutional Review Boards at Emory University and the University of Zambia approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…In the systematic review by Calvert and Ronsmans, 14 pregnancy was associated with HIV-related death among HIV-infected non-ART using women in five studies 16 , 17 , 33 , 39 (summary pooled RR = 1.65; 95% CI: 1.06, 2.57) although the single study from an African cohort did not find an association with time to HIV-related death in Rwandan women (aHR = 0.96; 95% CI: 0.48, 1.93). 33 Similarly, a study from Zambia published after this meta-analysis 40 found no association between time-varying pregnancy and all-cause mortality (the majority of which was HIV related) (aHR = 1.07; 95% CI: 0.68, 1.66) in non-ART using HIV-infected women. Our study was relatively small and, similar to other studies, had limited power to detect differences in disease progression by pregnancy; however, we were able to estimate a relatively precise date of infection giving us robust estimates of duration of infection.…”
Section: Discussionmentioning
confidence: 93%